Navigation system of Underwater Robotics Vehicle (URV) - Kam, Tony Boon Hoe (2008)
Inertial sensor like the AHRS (Attitude & Heading Reference System) output inertial data, acceleration and angular orientation. These data could be further processed to obtain position and velocity. However, the processed inertial data would drift over time due to the inherent sensor characteristics and inadequate compensation.